Investigation into the relation between geomagnetic data and earthquake occurrence using statistical approach / Nur Hidayah Ismail - Nur Hidayah , Ismail (2021)
Geoeffective solar events, especially the coronal mass ejection (CME) and the high-speed solar wind (HSSW) will induce geomagnetic storm upon its arrival to Earth. The solar events could trigger an earthquake occurred during the arrival. In this study, the focus is on the proxy of the geoeffective solar events, which is the geomagnetic Ap index and the data of shallow worldwide earthquakes. The main objective is to understand the interaction of the geoeffective solar activities and the occurrences of the shallow worldwide earthquake. Firstly, by examining the correlation between solar activities (total sunspot number, R and solar wind velocity, V) and the geomagnetic Ap index from 1994 until 2017. Secondly, through investigating the impact of a strong geomagnetic storm on the occurrences of the shallow earthquake by using the statistical approach, specifically, principal component analysis (PCA) and hierarchical cluster analysis (HCA). Lastly, a case study is done as supporting evidence for the interaction. The Ap index has a moderate positive relationship with V, where the value of the correlation coefficient is 0.54 and a negligible positive relationship with R, where the coefficient value is 0.14. Meanwhile, V and R show a negligible relationship with 0.04 coefficient value. Two groups were obtained from the PCA biplot: Group 1 - before the event (Day-4 to Day-1) and Group 2 - after the event group (Day 0 to Day+4). A two-cluster solution was obtained from the HCA, which shows that days before and after geostorm are divided into two main clusters. The statistical results show that earthquakes activity might have different behaviour before and after the geostorm occurred. In the September 2017 case study, the massive earthquake may appear to be due to the intense geoeffective solar events resulting from the strongest CME of solar cycle 24. In conclusion, this dissertation emphasizes that there are differences between days before and after the geostorm occurrence, hence, the solar influence upon earthquake occurrences cannot be neglected entirely.